The COMT Val158Met polymorphism regulates the effect of a dopamine antagonist on the feedback‐related negativity. (29th April 2014) - Mueller, Erik M.; Burgdorf, Christin; Chavanon, Mira‐Lynn; Schweiger, Desiree; Hennig, Jürgen; Wacker, Jan; Stemmler, Gerhard
Abstract Consistent with dopamine accounts of internal and external feedback processing, prior work showed that the dopamine D2 receptor antagonist sulpiride modulates the relationship between the dopaminergic COMT Val158Met polymorphism and the error‐related negativity (ERN). Here, we tested in an independent sample whether this Gene × Substance interaction generalizes to the feedback‐related negativity (FRN), which presumably shares underlying dopaminergic mechanisms with the ERN. N = 83 female participants genotyped for COMT Val158Met received 200 mg sulpiride versus placebo and performed a virtual ball‐catching task. The FRN to positive versus negative feedback was modulated by a significant COMT × Substance interaction. Mirroring prior work on the ERN, the tendency of the FRN to be more pronounced for VAL+ versus MET/MET carriers after placebo was reversed by sulpiride. The findings thus provide new evidence for dopaminergic models of feedback processing.